1991
DOI: 10.1172/jci115092
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids increase the synthesis of immunoglobulin E by interleukin 4-stimulated human lymphocytes.

Abstract: This study indicates that hydrocortisone (HC) Clin. Invest. 1991. 87:870-877.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
72
2

Year Published

1991
1991
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(79 citation statements)
references
References 36 publications
4
72
2
Order By: Relevance
“…However, since progesterone is unable to induce IgE synthesis in IL-4-stimulated PBMCs (ref. 22 and data not shown), these results suggest that GR is critical for upregulation of CD40L mRNA and for induction of IgE synthesis by HC.…”
mentioning
confidence: 65%
See 2 more Smart Citations
“…However, since progesterone is unable to induce IgE synthesis in IL-4-stimulated PBMCs (ref. 22 and data not shown), these results suggest that GR is critical for upregulation of CD40L mRNA and for induction of IgE synthesis by HC.…”
mentioning
confidence: 65%
“…Similar results were obtained with DM, which has relatively more pure GC activity than HC (data not shown). Progesterone, which fails to induce IgE synthesis in IL-4-stimulated B cells (22), failed to upregulate CD40L mRNA expression (data not shown).…”
Section: Figurementioning
confidence: 88%
See 1 more Smart Citation
“…Several groups have concluded that CS strongly potentiate IL-4-induced IgE synthesis by PBMC in vitro (25)(26)(27)(28), such that supplementation of culture medium with CS actually supplants the need for concomitant T cell help in IgE isotype switching (29). Using B cells from allergic patients, Bohle et al (30) have shown that this CS-mediated IgE production is polyclonal and cannot be attributed to the selective enhancement of allergen-specific IgE.…”
Section: Figurementioning
confidence: 99%
“…National Sagamihara Hospital, 18-1 Sakuradai, Sagamiiiara City, iCanagawa 228, Japan, 0 1995 Blackwell Science IgE production. This signal can be provided not only by activated CD4^ T cells [9,10], but also by Epstein Barr virus (EBV) infeclion [11], hydrocortisone [12,13], anti-CD40 MoAb [10,14]. CD40 ligand [15] or anti-CD58 MoAb [16].…”
Section: Introductionmentioning
confidence: 99%